Steam reforming of bio-oil derived small organics over the Ni/Al2O3 catalyst prepared by an impregnation–reduction method - Hu, Xun; Dong, Dehua; Zhang, L.; Lu, G. (Elsevier Science, 2014)
An impregnation–reduction method has been developed in this study to prepare the Ni/Al2O3 catalyst for steam reforming of bio-oil model compounds for hydrogen production. This method can alleviate the interactions be-tween nickel species and an alumina carrier and promote metal dispersion and utilization of the nickel species, achieving a highly active, selective and stable reforming catalyst. Moreover, this method is very simple and fast. Only the impregnation and reduction steps are involved and the catalyst can be prepared in situ. In addition, coke formation in steam reforming is not uniform on a catalyst bed. Coking in the topmost catalyst layer is much more serious.